The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1080/09553000410001669524
|View full text |Cite
|
Sign up to set email alerts
|

Novel radioprotectant drugs for sparing radiation‐induced damage to the physis

Abstract: Each drug reduced the amount of anticipated growth arrest in the animal model and some compared favourably in magnitude with that previously demonstrated for the established radioprotectant drug amifostine. Restoration of growth appears related to appearance of regenerative clones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Radiotherapy for bone or soft-tissue sarcomas close to the growth plate can result in the development of growth arrest, angular deformity, and/or limb length discrepancy. Potential for postirradiation recovery exists in the growth plate, based both on the variability of clinical outcomes following growth plate irradiation and on our own work in the weanling Sprague-Dawley (SD) rat model [Damron et al, 2000[Damron et al, , 2004a.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy for bone or soft-tissue sarcomas close to the growth plate can result in the development of growth arrest, angular deformity, and/or limb length discrepancy. Potential for postirradiation recovery exists in the growth plate, based both on the variability of clinical outcomes following growth plate irradiation and on our own work in the weanling Sprague-Dawley (SD) rat model [Damron et al, 2000[Damron et al, , 2004a.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, pentoxifylline had been shown to partially protect growth plate from the effect of phototherapy in a skeletally immature rat model. Earlier studies have indicated that pentoxifylline reduces oxygen radical production and protects against tissue damage in vivo by the action of its metabolites (20,21). The effects of pentoxifylline on membranes may explain its effects on cell deformability, inhibition of neutrophils priming by TNF-␣, diminished adherence and aggregation, reduced superoxide production, and improved locomotor responses (22).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several approaches may be required and be complementary, or perhaps even seem synergistic. For example, preclinical data suggest that other agents, such as pentoxifylline, misoprostol, IL-1-α , or selenium, may have synergistic effects when combined with amifostine [59] . Considering the proposed sigmoidal shape of most normal tissue complication probability curves ( Figure 3 ), reductions in normal tissue dose can have markedly different effects depending on where along the curve one lies.…”
Section: Expert Opinionmentioning
confidence: 99%